RESEARCH OF THE RELATIONSHIP BETWEEN THE WEIGHTED AVERAGE COST OF CAPITAL AND SELECTED PROFITABILITY RATIOS OF COMPANIES IN THE REPUBLIC OF SERBIA - Momčilović, Mirela; Vlaović Begović, Sanja; Jovin, Slobodanka (International Journal of Economic Practice and Policy, 2022)
The weighted average cost of capital (WACC) is determined as the weighted average cost of capital of all long-term sources of corporate financing. WACC is used as a discount rate when determining the value of a company, then in investment analysis when making a decision to accept/reject a project, as well as when evaluating the performance of top management. The paper calculates the WACC for all non-financial corporations that make up the basket of the Belex15 index and then examines the relationship between the weighted average cost of capital and the profitability ratios numbers ROA, ROE and net profit margin. The research results show that the WACC ranges between 3.45% and 17.77% for the sample companies. Also, the results show a negative correlation between WACC on one and selected profitability ratios on the other hand. However, it should be noted that this relationship is statistically significant only between WACC and net profit margin.